Model Pembelajaran Terbalik Berbasis Masalah (PTBM) Untuk Meningkatkan Kemampuan Berpikir Kreatif - Khaerudin (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2022)
The rapid development of ICT, on the one hand, provides many conveniences, but on the other hand, it often causes many problems. Furthermore, the development of science and technology also requires humans to be lifelong learners. Therefore, students must have the ability to use ICT (Technology Literate) and the ability to solve problems creatively. For this reason, a learning model is needed that integrates problem-solving skills, creative thinking, and mastery of technology. The integration of the flipped classroom model with problem-based learning reinforced with DO IT techniques is one of the alternative models to be developed. Based on these needs, this research will develop a learning model that integrates a problem-based learning model with a flipped classroom learning model, which is strengthened by applying to DO IT techniques. The learning model is called the Problem-Based Flipped Learning Model (PBFL Model). In realizing this model, research was conducted using the Gall and Borg development research model. Currently, development research is up to the revision stage based on the results of a learning expert review.